Temporal trends in cause-specific readmissions and their risk factors in heart failure patients in Sweden. (1st May 2020) - Cui, Xiaotong; Zhou, Jingmin; Pivodic, Aldina; Dahlström, Ulf; Ge, Junbo; Fu, Michael
Abstract: Background: It remains unclear whether readmissions of patients with heart failure (HF) have decreased over time in an era of improved therapy and management of HF. This study aimed to determine the temporal short- and long-term trends of cause-specific rehospitalization and their risk factors in a Swedish context. Methods: HF patients in the Swedish Heart Failure Registry (SwedeHF) were investigated. Maximum follow-up time was 1 year. Outcomes included the first occurrence of all-cause, cardiovascular (CV) and HF rehospitalizations. Cox proportional hazards models were performed to determine the impact of increasing years on risk for rehospitalization and its known risk factors. Results: Totally, 25, 644 index-hospitalized HF patients in SwedeHF from 2004 to 2011 were enrolled in the study. For 8 years, the incidence risk of 1-year all-cause rehospitalization remained unchanged, whereas the incidence risk of CV ( P  = 0.038) or HF ( P  = 0.0038) rehospitalization decreased. After adjustment for age and sex, a 3% decrease per every second year was observed for 1-year CV and HF rehospitalizations ( P  < 0.05). However, time to the first occurring all-cause, CV and HF rehospitalization did not change significantly from 2004 to 2011 ( P -values 0.13–0.87). When two study periods (2004–2005 vs. 2010–2011) were compared, the risk factor profile for rehospitalization was found to change. Conclusions: Throughout the 8-year study period, CV- and HF-related rehospitalizations decreased, whereas all-cause rehospitalization remained unchanged, indicating a parallel increase in non-CV rehospitalization in the HF patients. Highlights: Both cardiovascular- and heart failure-related rehospitalizations of patients with heart failure were declined All-cause rehospitalization remained unchanged, indicating increase of non-cardiovascular-related readmissions Risk factors for rehospitalization were found to change during the study period More efforts should be made in multidisciplinary heart failure management and targeting non-cardiovascular comorbidities